BEBERAPA PENDEKATAN SOSIOLOGIS DALAM PENELITIAN KARAWITAN - Suparno, T. Slamet (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
Basically, several approaches from many different fields of study, such as history, philosophy, anthropology, psychology, economy and sociology, can be applied in any researches, including a research on karawitan. This writing explains how sociological approach is applied to study karawitan. Principally, this approach analyze the relationship between society and karawitan art, its literary values and the social values, the artists’ background and the problems of art life in society. Several concepts and theories in sociology can be used to analyze karawitan as the object. Key words: karawitan (a Javanese music), art and sociological approach